Acquired Hepato Cerebral Degeneration An Atypical Finding in MRI of Brain mimicking Bilateral Ischaemic Stroke (Bangladesh Critical Care Journal, 2016)
Acquired Hepatocerebral Degeneration (AHD) produces a panel of neurological symptoms occurring in patients with chronic liver disease. These symptoms may mimic different neurological abnormalities e.g. abnormal movements, rigidity, parkinsonism, ataxia, neuropsychiatric and cognitive manifestations.[1] Acquired Hepatocerebral Degeneration is usually encountered in patients with CLD due to accumulation of manganese & other metabolic toxins in basal ganglia, following repeated episodes of liver failure[2] .The aim of this case report is to highlight the MRI finding of Acute Hepatocerebral Degeneration which often can be underappreciated owing to the possibility of diagnosing a relatively common condition that is Bilateral Ischemic stroke.[19].Bangladesh Crit Care J March 2016; 4 (1): 54-57